HAEMATOLOGICAL AND SERUM BIOCHEMICAL INDICES OF BROILER CHICKENS FED FOUR DIFFERENT COMMERCIAL DIETS - Abdulhamid, S.; Mai, H. M.; Kalla, D. J. U. (Nigerian Journal of Agriculture and Agricultural Technology, 2024)
The study was conducted to determine the haematological and serum biochemical components of broiler chickens fed four different commercial diets. Two hundred and eight (208) day-old chicks were allotted to four diets in replicates of four in a completely randomized design (CRD). Each replicate had 13 birds and the diets were designated as A, B, C, and D. Feed and water were supplied ad libitum and the trial lasted for 42 days. Results for haematological indices showed no significant influence of the diets except for lymphocytes and basophils. Percentage lymphocytes was higher (P<0.05) on diet A (39.50%) which was statistically similar with diets B (38.75%) and D (34.75%) but lower in diet C (33.25%). Similarly, the level of basophils was higher (P<0.05) in diet D (3.50%) but statically similar to diets A (2.25%) and C (2.25%) and lower in diet B (1.00%). However, diet B did not differ statistically from diets A and C. None of the serum biochemical indices revealed any significant influence of diet. It was concluded that the four different commercial diets did not pose any health risk on broiler chickens and therefore are recommended for broiler production.